2012
DOI: 10.1007/s00508-012-0209-y
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant use of beta-1 adrenoreceptor blocker and norepinephrine in patients with septic shock

Abstract: Saving the heart 30 beats/min did not demonstrate adverse impact on global haemodynamics in rates above 110/min. Using well titratable betablocker seems to be safe and cardioprotective in septic shock patients with high cardiac output.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 17 publications
2
48
0
1
Order By: Relevance
“…Esmolol tended to increase stroke volume which resulted in no significant decrease in CO or CI during esmolol administration. A continuous betablockade did not induce significant changes in DO 2 , VO 2 or OER [97,98]. A similar impact on haemodynamics was reported by Morelli who used a very low dosage of 100 mg h -1 as part of the applied EGDT protocol with no echocardiography or verification of the absence of contraindications to a betablocker.…”
Section: Beta-blockerssupporting
confidence: 50%
See 2 more Smart Citations
“…Esmolol tended to increase stroke volume which resulted in no significant decrease in CO or CI during esmolol administration. A continuous betablockade did not induce significant changes in DO 2 , VO 2 or OER [97,98]. A similar impact on haemodynamics was reported by Morelli who used a very low dosage of 100 mg h -1 as part of the applied EGDT protocol with no echocardiography or verification of the absence of contraindications to a betablocker.…”
Section: Beta-blockerssupporting
confidence: 50%
“…Nevertheless, the comparisons to control patients were fraught with high mortality in the control group while the haemodynamic monitoring did not include echocardiography [87]. Several limitations have to be considered including the absence of echocardiographic cardiac function evaluation and the exclusion of the valve and conduction disorders, prior to beta-blocker administration in septic shock patients [88,90]. The same limitations regarding the absence of echocardiographic screening of cardiac function and haemodynamics exist in all the case series on various antiarrhythmic agents in sepsis and septic shock patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one RCT enrolled a large number of patients (154) patients) 8 , while the other was smaller (41 patients) and published in Chinese language 11 . Other two peer-reviewed prospective studies 12,13 were fairly small (respectively 25 and 10 patients) and they did not include a control group. Therefore, in consideration of the imbalance in the sample size between these studies, the absence of a control group in two studies, a metaanalysis will be not meaningful at this stage.…”
Section: Discussionmentioning
confidence: 98%
“…While it is theoretically plausible, experimental and clinical studies yielded conflicting results (5)(6)(7)48,49). Observational studies showed that esmolol, the most commonly used beta-blocker in septic shock, was associated with economization of cardiac work and oxygen consumption.…”
Section: Beta-blockersmentioning
confidence: 99%